Pomegranate (Punica granatum) peel fractions obtained by supercritical CO2 increase oxidative and colour stability of bluefish (Pomatomus saltatrix) patties treated by UV-C irradiation. (15th November 2021) - Silva, Laís de O.; Garrett, Rafael; Monteiro, Maria Lúcia G.; Conte-Junior, Carlos A.; Torres, Alexandre G.
Graphical abstract: Highlights: Pomegranate peel is a rich source of natural antioxidants and bioactive compounds. Sequential fractionation by supercritical CO2 was used to separate the antioxidants. Fractionation resulted in a lipid fraction, and one or two phenolic fractions. Extract and fractions were used in bluefish to assess the oxidative stability. Pomegranate peel fractions are promising as natural preservatives in fish meat. Abstract: The sequential fractionation by supercritical-CO2 (SC-CO2 ) was applied to obtain fractions enriched in bioactive compounds of pomegranate peel, and we investigated if pomegranate peel extract and fractions would be effective to inhibit lipid and protein oxidation, and discolouration of bluefish patties stored at 4 °C for 9 days, after UV-C irradiation. The non-fractionated SC-CO2 extract from pomegranate peel was rich in phenolic compounds, mainly ellagitannins, besides, it possessed lipophilic compounds such as tocopherols and β-carotene. These compounds were successfully separated by the fractionation protocols, in a lipid fraction concentrated in lipophilic compounds, and one or two fractions enriched with phenolic compounds, especially ellagitannins. The lipid fraction and the high phenolics fraction from pomegranate peel were then as effective as the synthetic antioxidant BHT in avoiding bluefish patties oxidation during refrigerated storage. Our data indicates that pomegranate peel fractions could be used to replace a synthetic antioxidant in fish meat.